Rumah Pintar Pemilu Kampar dan Peningkatan Literasi Politik Peserta Didik Tingkat SMA - Olifvia Fajrin; Sri Erlinda; Hariyanti Hariyanti (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
This study aims to describe the role of the Kampar Election Smart House (ESH) in increasing the political literacy of high school level students. This study used qualitative research methods . As for the data and data sources used in this study using primary data and secondary data. Primary data from this study came from the results of in-depth interviews with staffs at ESH Kampar and observations of the activities. This research was carried out because of the low level of political literacy of students. There are still many students who are apathetic, this is due to the low level of political literacy. The results of this research is Kampar's ESH played a role in increasing the political literacy of students at the high school level. Kampar’S ESH provides education about democratic, electoral values, and other political values ​​such as providing education about the state and power, Activities of political institutions of authority and their role trains expressing opinions, government regulations and public services, and involves students in activities politics. The limitations of this research is Kampar’s ESH is doing political literacy in one state high school. Though there are 51 high school in this regency.